2004
DOI: 10.1111/j.1467-839x.2004.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimism across cultures: In response to the severe acute respiratory syndrome outbreak

Abstract: Based on our early research, we predicted that the Chinese may be more optimistic and less pessimistic than North Americans in response to negative life events. A survey was conducted to investigate optimism cross culturally in the context of the severe acute respiratory syndrome (SARS) outbreaks in Canada and China. Chinese students in Beijing and European Canadians in Toronto answered questions about their perceptions of SARS. No significant cultural difference was found on dispositional optimism, as measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
2
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 15 publications
8
107
2
9
Order By: Relevance
“…These findings confirm the previous results found on adult samples, showing that optimistic individuals were more likely to expect more positive events to happen to them in the future (e.g., Blackwell et al, 2013;Sharot et al, 2007). In line with the studies reported on adult samples (e.g., Ji et al, 2004;Radcliffe & Klein, 2002), dispositional optimism did not significantly correlate with the likelihood of judgements of future events. All these findings suggest that, although a high level of optimism increases the beliefs that future positive events are more likely to happen in the future, it did not implicitly generate the beliefs that negative events are less likely to occur in the future.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings confirm the previous results found on adult samples, showing that optimistic individuals were more likely to expect more positive events to happen to them in the future (e.g., Blackwell et al, 2013;Sharot et al, 2007). In line with the studies reported on adult samples (e.g., Ji et al, 2004;Radcliffe & Klein, 2002), dispositional optimism did not significantly correlate with the likelihood of judgements of future events. All these findings suggest that, although a high level of optimism increases the beliefs that future positive events are more likely to happen in the future, it did not implicitly generate the beliefs that negative events are less likely to occur in the future.…”
Section: Discussionsupporting
confidence: 82%
“…Studies conducted on adult samples showed that the optimists display more positive life evaluations than pessimists and were less likely to expect negative events in the future, such as unsafe work practices, overweight or dental health problems (e.g., Fowler & Geers, 2015;Gherasim et al, 2016;OginskaBulik & Juczynski, 2001). Other studies found no association between dispositional optimism and judgements of negative events, such as perceiving the risk of heart attack, obesity or severe acute respiratory syndrome on samples of adults (e.g., Geers et al, 2013;Radcliffe & Klein, 2002) and undergraduate students (e.g., Ji, Zhang, Usborne, & Guan, 2004). Moreover, previous literature consistently showed that adults with a high level of dispositional optimism were more likely to expect more positive events to happen to them in the future (e.g., Blackwell et al, 2013;Sharot, Riccardi, Raio, & Phelps, 2007).…”
Section: Dispositional Optimismmentioning
confidence: 86%
See 1 more Smart Citation
“…Esta definición implica que, tanto el optimismo como el pesimismo, son rasgos relativamente estables, consistentes a través del tiempo y las situaciones. Por tal motivo, Scheier y Carver (20) hacen referencia al optimismo disposicional para referirse a una creencia o expectativa generalizada, que se mantiene estable en el tiempo, de que ocurrirán sucesos positivos (21) . Son diversos los estudios que han corroborado la relevancia y utilidad del constructo optimismo, ya que permite predecir variables y estados de considerable importancia en Psicología Clínica (17,22) .…”
Section: Introductionunclassified
“…That is, lowering bad cholesterol in the high condition and increasing good cholesterol in the low condition are both desirable, and Chinese participants might have predicted more change than Canadians because they are more optimistic and hopeful in such a context (see Ji, Zhang, Usborne & Guan, 2004). …”
Section: Studymentioning
confidence: 99%